Histopathological Implications of Aspergillus Infection in Lung - Tochigi, Naobumi; Okubo, Yoichiro; Ando, Tsunehiro; Wakayama, Megumi; Shinozaki, Minoru; Gocho, Kyoko; Hata, Yoshinobu; Ishiwatari, Takao; Nemoto, Tetsuo; Shibuya, Kazutoshi (Mediators of Inflammation, 2013)
This paper opens with a discussion on the significance of invasive fungal infections in advanced contemporary medicine, with an emphasis on the intractability of disease management and the difficulties of diagnosis. This is followed by a discussion concerning classification, histopathological features, and pathophysiology. While it has been largely accepted that Aspergillus species is recognized by cellular receptors and attacked by neutrophils, the radiological and macroscopic findings linking infection with neutropenia remain unconfirmed. In an effort to gain a better understanding of the pathophysiology and pathogenesis of invasive aspergillosis, we wish to emphasize the utility of radiological and histopathological examinations since these can provide detailed information on the extremely complex interaction between the causative microbes and tissue responses. A review of noninvasive or semi-invasive aspergillosis is also provided, with particular emphasis on chronic necrotizing pulmonary aspergillosis, which is recognized as a transition form of simple pulmonary aspergilloma and invasive pulmonary aspergillosis, although few findings have been reported in this area.